SDF Mathematical Model as a Solution to Overcoming Difficulties in Completing Thesis of Students of Mathematics Department of Makassar State University - Wahidah Sanusi; Syafruddin Side; Muh. Ishaq Firdaus (Journal of Mathematics, Computations and Statistics, 2026)
This study aims to develop and analyze the SDF mathematical model in addressing difficulties faced by students in completing their theses at the Mathematics Department, Universitas Negeri Makassar, in 2023. The SDF model is derived from the SIR model, which is commonly utilized to analyze disease spread, by adapting specific assumptions relevant to the students' circumstances. The analysis of the model focuses on determining equilibrium points, model stability, and the basic reproduction number , which serves as a critical parameter in understanding the dynamics of the issue's spread. Data for the study were collected from students in the Mathematics Department, Faculty of Mathematics and Natural Sciences, Universitas Negeri Makassar, and were used for model simulations employing Maple 18 software. The analysis results indicate a basic reproduction number value of , implying that the number of students experiencing difficulties in completing their theses is expected to increase over time without intervention. These findings provide valuable insights for the university to comprehend the factors influencing the thesis completion rates among students. It is anticipated that this study can inform the design of more effective strategies and interventions to assist students in overcoming their challenges. The SDF model can also serve as a reference for similar studies in other contexts